2009
DOI: 10.1038/sc.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Soluble complement receptor type 1 inhibits complement system activation and improves motor function in acute spinal cord injury

Abstract: Study design: Spinal cord injured rat model, treated with soluble complement receptor type 1 (sCR1). Setting: Experimental Animal Department of China Medical University, Shenyang, China. Objectives: Soluble CR1 is a powerful inhibitor of complement activation. In this study, we investigate the effectiveness of sCR1 on spinal cord injury (SCI) in rats. Methods: Spinal cord injury was induced in Sprague-Dawley rats. Three experimental groups were examined; the sCR1 group was administered sCR1 at 1 h after the SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The effect of inhibiting the classical/alternative pathway [143] and C3b/C4b activity [144] was investigated in Sprague–Dawley rats subjected to moderate weight-drop SCI. In these studies, treated animals had decreased complement deposition and leukocyte infiltration, which was paralleled by increased tissue sparing and improved locomotor recovery compared to vehicle-treated animals subjected to SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inhibiting the classical/alternative pathway [143] and C3b/C4b activity [144] was investigated in Sprague–Dawley rats subjected to moderate weight-drop SCI. In these studies, treated animals had decreased complement deposition and leukocyte infiltration, which was paralleled by increased tissue sparing and improved locomotor recovery compared to vehicle-treated animals subjected to SCI.…”
Section: Introductionmentioning
confidence: 99%
“…5 In other studies, complement inhibition at the C3 activation step with vaccinia virus complement control protein (VCP), 8 soluble CR1, 10 and a targeted form of Crry 7 were all protective against SCI and improved functional recovery. More recent studies have shown that C1q deficiency and C1-inhibitor are protective in models of SCI, 9,11 indicating an important role for the classical pathway.…”
Section: Post-traumatic Inflammation After Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Early studies showed that patients with spinal cord injury have elevated complement levels in their sera, 4 and more recent studies have used rodent models to demonstrate a role for complement in SCI. These studies include analysis of complement activation and deposition after SCI [5][6][7] and the demonstration that complement inhibition [7][8][9][10] or complement deficiency 7,11 ameliorates injury and improves functional recovery after traumatic injury.…”
Section: Post-traumatic Inflammation After Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…166,167 Also in SCI, sCR1 decreased inflammatory reactions and improved motor function post-acute neurotrauma. 168 In a clinical trial of 59 lung transplant patients, the administration of TP-10, a soluble complement receptor 1 inhibitor, resulted in a decrease in the duration of mechanical ventilation compared to patients receiving a placebo. 169 Another clinical trial of 564 high-risk patients undergoing cardiac surgery showed that TP-10 reduced the incidence of mortality and MI particularly in male patients.…”
Section: Strategic Approaches Of Complement Inhibitionmentioning
confidence: 99%